A relação das tendinopatias do manguito rotador com as atividades cotidianas: uma contribuição para o design ergonômico - Pereira, Diego Dalvan [UNESP] (2015)
Movements and postures performed domestically with household activities can cause injury to the shoulders, including the rotator cuff tendinopathy (RCT). Interdisciplinarity is fundamental for prevention of RCT, which affect mainly women after the fourth decade of life, and are caused, among other factors, by activities that require elevation of the upper limbs. This cross-sectional study aimed to demonstrate the importance of ergonomic intervention in the prevention of RCT in our daily activities, performed in homes and possible parameters to assist the ergonomic design and/or redesign of products that may be contributing to te development of these disorders. For data analysis were used descriptive statistics as the mean, standard deviation (SD) and percentage rate (%). Methods of inferential statistics such as Fisher's exact test and the chi-square test for multiple comparisons were also applied. All statistical tests were used considering a significance level of 0.05. Participated in the first stage of the study 344 subjects, where 69.5% were female, age ranged from 18 to 83 years, and 49.4 of average age year. The majority of the sample (76,4%) was in the age group of 40 years old and higher. There was evidence of the association of pain symptoms in the shoulder with the variables: has woken up in pain, did not perform surgery and dominant right upper limb. Housework is performed by 74.1% (255), where only 13.4% (46) of those were male. From the inclusion criteria, 64 individuals were selected for the second stage of research, in which was conducted an ergonomic research in their homes. Based on partial results it is concluded that some upper limbs postures adopted for use on handling of utensils, mainly by women during household chores, including sleep posture, are inadequade from a biomechanical and ergonomic point of view, since this overexposes a high risk of RCT